Extending cognitive development research to create more equitable science learning contexts - Kumar, Sona C.; Haber, Amanda S. (Frontiers in Developmental Psychology, 2025)
This paper aims to examine how the field of cognitive development has shifted over the last 15 years or so to consider implications of basic research in the field for educational settings, specifically in science education. Focusing on informal learning contexts, we argue that cognitive development researchers have an opportunity to build upon the work of the last fifteen years in a few critical ways. The paper examines theoretical frameworks driving research at the intersection of cognitive development and science education and reviews current research related to early science learning. We then discuss future directions for researchers aimed at creating more equitable science learning contexts for young children, including diversifying samples, forging sustainable community partnerships, and rethinking science and science education. Taken together, this paper has the potential to provide new directions for researchers, practitioners, and policymakers at the intersection of cognitive development and science education.